High-Quality Genomes of Pangolins: Insights into the Molecular Basis of Scale Formation and Adaption to Myrmecophagous Diet. (31st December 2022) - Yan, Dingyu; Luo, Xier; Tang, Jiabin; Xu, Shanghua; Huang, Kongwei; Wang, Xiaobo; Feng, Tong; Que, Tengcheng; Jia, Miaomiao; Guo, Xiaobing; Rehman, Saif ur; Li, Zhipeng; et al.
Abstract: Pangolins are one of nature's most fascinating species being scales covered and myrmecophagous diet, yet relatively little is known about the molecular basis. Here, we combine the multi-omics, evolution, and fundamental proteins feature analysis of both Chinese and Malayan pangolins, highlighting the molecular mechanism of both myrmecophagous diet and scale formation, representing a fascinating evolutionary strategy to occupy the unique ecological niches. In contrast to conserved organization of epidermal differentiation complex, pangolin has undergone large scale variation and gene loss events causing expression pattern and function conversion that contribute to cornified epithelium structures on stomach to adapt myrmecophagous diet. Our assemblies also enable us to discover large copies number of high glycine-tyrosine keratin–associated proteins (HGT-KRTAPs). In addition, highly homogenized tandem array, amino content, and the specific expression pattern further validate the strong connection between the molecular mechanism of scale hardness and HGT-KRTAPs.